Impact of singular versus combinatorial environmental stress on RONS generation in Drosophila melanogaster larvae - Bomble, Pratibha; Nath, Bimalendu B. (Frontiers in Physiology, 2024)
We investigated environmentally correlated abiotic stressor desiccation (D), heat (H), and starvation (S) in the generation of reactive oxygen and nitrogen species (RONS) using Drosophila melanogaster larvae as an experimental model, subjected to either individual stressors or exposed to a combinatorial form of stressors (D + H, H + S, and D + S). The study was also extended to find synergistic endpoints where the impacts of all three stressors (D + H + S) were exerted simultaneously. We estimated the lethal time (LT20) at specific doses using regression and probit analyses based on the larval survival. LT20 values were used as the base-level parameter for further oxidative stress experimental analysis work. First, all stressors led to the activation of a typical common oxidative stress-mediated response irrespective of the mode of exposure. As envisaged, D. melanogaster larvae exhibited a homeostatic stress tolerance mechanism, triggering an antioxidant defense mechanism, indicated by an elevated level of total antioxidant capacity and enhanced activities of superoxide dismutase, catalase, glutathione reductase, and glutathione peroxidase. In all types of stress-exposed regimes, we found a negative impact of stressors on the activity of mitochondrial enzyme aconitase. Elevated levels of other oxidative stress markers, viz., lipid peroxidation, protein carbonyl content, and advanced oxidative protein products, were obvious although the increment was treatment-specific. Desiccation stress proved to be the most dominant stressor compared to heat and starvation. Among the combination of stressors, rather than a single stressor, D + H impacted more than other binary stress exposures. Focusing on the impact of singular versus combinatorial stress exposure on RONS generation, we observed an increase in the RONS level in both singular and combinatorial forms of stress exposure although the magnitude of the increment varied with the nature of stressors and their combinations. The present study indicated an “additive” effect when all three stressors (D + H + S) operate simultaneously, rather than a “synergistic” effect.